Production and Role of Nitric Oxide in Endometrial Cancer - Seung Geun Yeo; Yeon Ju Oh; Jae Min Lee; Joon Hyung Yeo; Sung Soo Kim; Dong Choon Park (Antioxidants)
Endometrial cancer ranks as the fourth most common cancer among women in the United States. While early-stage treatment is generally effective with a cure rate of approximately 90%, the five-year survival rate dramatically decreases to 10–15% for advanced-stage diagnoses. Consequently, ongoing research seeks to improve treatment outcomes for endometrial cancer. Nitric oxide (NO) is implicated in various biological processes, including cancer progression, and is believed to play a significant role in human endometrial cancer. However, its specific function remains controversial. This study aims to elucidate the effects of NO in endometrial cancer through a comprehensive literature review. A thorough review of the literature was conducted using Cochrane Libraries, EMBASE, Google Scholar, PubMed, and SCOPUS databases to assess the induction and role of NO in the development of endometrial cancer. Out of 33 initially reviewed articles, 7 studies were included in the final review after excluding those unrelated to endometrial cancer or NO. Of these, six studies (85.7%) reported increased NO levels in endometrial cancer, whereas one study (14.3%) noted decreased NO levels or a defensive mechanism role. NO production was linked to tumor-promoting effects such as invasiveness, metastasis, angiogenesis, interaction with omental adipose stromal cells (O-ASCs), adipogenesis, and mitochondrial suppression. Conversely, NO also exhibited tumor-suppressive effects, including cell-cycle arrest, apoptosis induction, promotion of cancer stem-like cells, and upregulation of tumor suppressor genes like CDKN1A and RASSF1A. NO production is associated with the pathogenesis, development, and prognosis of endometrial cancer, with effects varying based on NO level fluctuations. Differences in NO production and function were observed according to the type of nitric oxide synthase (NOS) involved, control conditions, subtype, grade, and invasiveness of the cancer, as well as the experimental methodologies employed. NO demonstrated dual action in endometrial cancer: low concentrations promoted tumor growth by protecting cells and inhibiting apoptosis, while high concentrations exerted cytotoxic effects, suppressing tumor growth. However, no studies have precisely defined the concentration thresholds or mechanisms by which NO contributes to either tumorigenesis or tumor suppression in endometrial cancer. To effectively harness the therapeutic potential of NO in treating endometrial cancer, a deeper understanding of these dual-effect mechanisms is necessary.